Analisis Pengaruh Bilangan Reynold Terhadap Efisiensi Kondensor Heat Exchanger Menggunakan Simulasi CFD - Diana Kamaliyah Ichsan (Institut Teknologi Sains Bandung, 2023)
A condenser is a type of mechanical equipment that functions to convert hot steam into water by using sea water or lake water as a cooling medium. One of the uses of the condenser in Steam Power Plants is a Shell & Tube Heat Exchanger. The efficiency of the condenser is assessed by the greater the temperature drop that occurs at the output of hot steam from the turbine. In this research, a 3D simulation method with Computational Fluid Dynamics (CFD) was used to determine the effect of Reynold Number (Re) variations of 1000, 2000, and 4000 on residual graphs, temperature and pressure drop values, and pathlines. fluid flow. The simulation results show that the decrease in steam temperature in simulations with Re 1000 and Re 4000 is relatively the same, namely -96.9K, while at Re 2000 the decrease in steam temperature is -30.3K. The increase in water temperature at Re 1000 is 30.9K, Re 2000 is 43.03K, and Re 4000 is 3.7K. It can be concluded that the simulation with Re 4000 is the experiment with the best quality because the increase in air temperature is the smallest with the largest decrease in heat in the steam fluid